Climate change policy responses for Canada's Inuit population: The importance of and opportunities for adaptation - Ford, J D; Pearce, T; Duerden, F; Furgal, C; Smit, B (Global Environmental Change, 2010)
We identify and examine how policy intervention can help Canada's Inuit population adapt to climate change. The policy responses are based on an understanding of the determinants of vulnerability identified in research conducted with 15 Inuit communities. A consistent approach was used in each case study where vulnerability is conceptualized as a function of exposure-sensitivity to climatic risks and adaptive capacity to deal with those risks. This conceptualization focuses on the biophysical and human determinants of vulnerability and how they are influenced by processes and conditions operating at multiple spatial-temporal scales. Case studies involved close collaboration with community members and policy makers to identify conditions to which each community is currently vulnerable, characterize the factors that shape vulnerability and how they have changed over time, identify opportunities for adaptation policy, and examine how adaptation can be mainstreamed. Fieldwork, conducted between 2006 and 2009, included 443 semi-structured interviews, 20 focus groups/community workshops, and 65 interviews with policy makers at local, regional, and national levels. Synthesizing findings consistent across the case studies we document significant vulnerabilities, a function of socio-economic stresses and change, continuing and pervasive inequality, and magnitude of climate change. Nevertheless, adaptations are available, feasible, and Inuit have considerable adaptive capacity. Realizing this adaptive capacity and overcoming adaptation barriers requires policy intervention to: (i) support the teaching and transmission of environmental knowledge and land skills, (ii) enhance and review emergency management capability, (iii) ensure the flexibility of resource management regimes, (iv) provide economic support to facilitate adaptation for groups with limited household income, (v) increase research effort to identify short and long term risk factors and adaptive response options, (vi) protect key infrastructure, and (vii) promote awareness of climate change impacts and adaptation among policy makers.